2016
DOI: 10.1186/s12917-016-0823-4
|View full text |Cite
|
Sign up to set email alerts
|

Pigs immunized with a novel E2 subunit vaccine are protected from subgenotype heterologous classical swine fever virus challenge

Abstract: BackgroundClassical swine fever (CSF) or hog cholera is a highly contagious swine viral disease. CSF endemic countries have to use routine vaccination with modified live virus (MLV) vaccines to prevent and control CSF. However, it is impossible to serologically differentiate MLV vaccinated pigs from those infected with CSF virus (CSFV). The aim of this study is to develop a one-dose E2-subunit vaccine that can provide protection against CSFV challenge. We hypothesize that a vaccine consisting of a suitable adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(79 citation statements)
references
References 31 publications
3
73
0
3
Order By: Relevance
“…In this work, we demonstrated that a N. benthamiana ‐derived CSFV E2 vaccine protected pigs from a lethal CSFV challenge, even after a single‐dose vaccination as recently demonstrated in pigs vaccinated with insect‐derived E2 formulated with KNB adjuvant (Madera et al ., , ) Robust anti‐E2 IgG and CSFV‐neutralizing antibody responses were generated in vaccinated pigs. Pig groups receiving two doses of E2 vaccine showed no clinical signs, low or no viremia in serum and nasal swabs and continuous weight gain post challenge.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this work, we demonstrated that a N. benthamiana ‐derived CSFV E2 vaccine protected pigs from a lethal CSFV challenge, even after a single‐dose vaccination as recently demonstrated in pigs vaccinated with insect‐derived E2 formulated with KNB adjuvant (Madera et al ., , ) Robust anti‐E2 IgG and CSFV‐neutralizing antibody responses were generated in vaccinated pigs. Pig groups receiving two doses of E2 vaccine showed no clinical signs, low or no viremia in serum and nasal swabs and continuous weight gain post challenge.…”
Section: Discussionmentioning
confidence: 99%
“…We formulated pE2 with one of two adjuvants: (i) TS6 and (ii) KNB (Kansas State University, Manhattan, KS). In addition, efficacy was determined with these pE2 adjuvant formulations and an insect cell-derived E2 (iE2) KNB-adjuvanted vaccine, KNB-E2 (Madera et al, 2016). The six treatment groups are summarized in Table 1.…”
Section: Plant-made E2 Confers Full Protection Against Wild-type Csfvmentioning
confidence: 99%
See 2 more Smart Citations
“…Another example is classical swine fever virus (CSFV). It has been demonstrated that the E2 viral protein produced in the baculovirus expression system induces the synthesis of CSFV-neutralizing antibodies in pigs [23].…”
Section: Peptides As Protective Antigensmentioning
confidence: 99%